Práticas informacionais sob a ótica de um problema da juventude - Juliane Teixeira Silva Magalhaes (2005)
This work deals with the practice of information between the young of the urban periphery, having relative questions to the precocious pregnancy as thematic clipping. The investigated young are living of Ribeirão das Neves, city of the Metropolitan Region of Belo Horizonte, borough marked by serious socio-cultural and economic problems. Under this context, the practice of information was analyzed in the sphere of the cultural dynamic, of the daily life. The theoretical landmark is based in an anthropologic reading of the information, tracing different readings regarding the informational citizen. The empirical field is boarded by the qualitative methodology, using the technique of focal groups. For analysis and interpretation of the data, a "Guide for study of the process of assimilation of information" was developed, and, under the light of the theoretical referential, it made possible, among others proved evidences, to identify some ways of how the citizens (young) deal with the information, knowing that, in the universe of the youth of the urban periphery, the biggest influence is given by the television and orally.